Ideological systems and its validation: a neutrosophic approach - Josué Nescolarde-Selva; José Luis Usó-Doménech (Neutrosophic Sets and Systems, 2015)
Ideologies face two critical problems in the reality,the problem of commitment and the problem of validation.Commitment and validation are two separate phenomena, inspite of the near universal myth that the human is committedbecause his beliefs are valid. Ideologies not only seem externaland valid but also worth whatever discomforts believing entails.In this paper the authors develop a theory of social commitmentand social validation using concepts of validation of neutrosophic logic.